Budapest Art Expo : 1991. - Budapest Art Expo Budapest 1991 (Budapest : Budapest Art Expo Foundation, 1991)
Abraham, Rafael ; Adam, Zoltan ; Bak, Imre ; Balind, Istvan ; Barabas, Marton ; Bartha, Jozsef ; Bernat, Andras ; Birkas, Akos ; Biro, Gabor ; Bodoczky, Istvan ; Budahelyi, Tibor ; Bujdoso, Erno ; Bullas, Jozsef ; Bunus, Ioan ; Burtas, Viktor ; Dumanic, Zlatan ; ef Zambo, Istvan ; etc.
Budapest Art Expo 1991, Budapest Art Expo Foundation, March 15-20, 1991
boek